Sustainability and Health Promoting Universities: an integrative literature review on the possibilities and challenges in this interface - Terra, Luana Aparecida Goulart; Nunes , Sarah Trevisan; Toledo, Renata Ferraz De (Technical and Scientific Journal Green Cities, 2025)
Objective: This study aimed to investigate, within the scientific literature, how sustainability principles and practices are being incorporated into the experiences of Health Promoting Universities (HPU). Methodology: An integrative literature review with a qualitative approach, conducted through searches in the CAPES Journals Portal, PubMed, and Google Scholar databases, using the descriptors "health promoting university” AND “sustainability” OR “sustainable development” OR “Agenda 2030,” covering the period from 2015 to 2025. The critical analysis of the 27 selected articles was guided by two main frameworks: the Okanagan Charter (2015), which provides normative reference, guidelines, and principles for the HPU movement; and Van den Hove’s (2007) science–policy–society interface model, which helps to understand the institutional challenges of sustainability in complex contexts. Originality/Relevance: The study addresses a theoretical and methodological gap that remains scarcely explored: the concrete articulation between health, sustainability, and higher education. It reinforces the role of universities as strategic spaces for promoting planetary health, social justice, and ecological transition, contributing to the advancement of the 2030 Agenda goals. The analysis highlights the low degree of institutionalization of the Okanagan Charter guidelines and the fragmentation of sustainable actions in universities, demonstrating the critical originality of the research. Results: A predominance of occasional and theoretical experiences; few empirical studies detail integrated practices of sustainability and health promotion. Significant participation of students and faculty; low involvement of technical staff, administrators, and surrounding communities. Progress in curricular mainstreaming and the emergence of institutional sustainability policies in some institutions. Lack of systematized analysis and evaluation indicators—quantitative or qualitative—and of monitoring strategies for impacts. Theoretical/Methodological Contributions: Organization and critical presentation of previously scattered data, with an innovative categorization that articulates international frameworks (SDGs, Okanagan Charter) with institutional practices. Suggests methodological pathways for future research on sustainable HPUs, with emphasis on assessing cognitive, environmental, social, and institutional impacts. Proposes broadening the concept of the university as a “living ecosystem” committed to sociopolitical and ecological transformation. Social and Environmental Contributions: Highlights the potential of universities as catalysts for sustainable change and promoters of collective well-being. Emphasizes the importance of community participation and democratic governance in building healthy and inclusive environments. Provides input for strengthening university practices committed to the SDGs, fostering an institutional culture based on equity, co-responsibility, and environmental justice.